Assessment of Achilles Tendon Changes After Long‐Distance Running Using Ultrashort Echo Time Magnetization Transfer MR Imaging. Issue 3 (21st January 2022) - Fang, Yijie; Zhu, Dantian; Wu, Wenhao; Yu, Wenjun; Li, Shaolin; Ma, Ya‐Jun
Abstract : Background: Long‐distance running is a common cause of Achilles tendinopathy. A reliable magnetic resonance imaging (MRI) technique to track early changes in the tendon caused by running could facilitate more effective interventions to combat progression. Purpose: To evaluate an ultrashort echo time sequence with magnetization transfer preparation (UTE‐MT) in the detection of changes in Achilles tendons of amateur marathon runners before and after long‐distance running. Study Type: Prospective. Population: Thirty‐two runners (19 enrolled for full marathons and 13 enrolled for half‐marathons) and 5 healthy non‐runners. Field Strength/Sequence: 3.0 T; UTE‐MT and dual‐echo UTE for T2* assessment (UTE‐T2*). Assessment: MRI was performed 1‐week pre‐race, 2‐days post‐race, and 4‐weeks post‐race. UTE‐MT ratio (UTE‐MTR) and UTE‐T2* of tendon were measured by two independent radiologists who were blinded to the scan time point and participant data. The Achilles tendon was divided into six regions of interest (ROIs) for data analysis, namely the insertion part (INS), middle part (MID), muscle‐tendon junction (MTJ), tendon‐bone insertion (TBI), tendon‐muscle insertion (TMI), and whole tendon (bulk). Statistical Tests: Analysis of variance and Friedman's rank tests were used to evaluate changes in UTE‐MTR and UTE‐T2* between time points. Tukey test and Bonferroni method were used for further comparisons. P < 0.05 was considered significant. Results: The UTE‐MTR values of most tendon ROIs changed significantly between the measured time points, except for the INS region ( P = 0.1977). Conversely, the UTE‐T2* values only showed significant changes in the MID and TBI regions. Paired comparisons showed that the UTE‐MTR decreases in the MTJ, MID, TMI, and bulk regions at 2‐days post‐race were significant compared to measures taken pre‐race and 4‐weeks post‐race. For UTE‐T2* measurements, significant differences were observed only for the MID region between pre‐race and 2‐days post‐race ( P = 0.0408, 95% CI: 0.0061, 0.1973), and for the TBI region between pre‐race and 4‐weeks post‐race ( P = 0.0473, 95% CI: 0.0013, 0.1766). Data Conclusion: The UTE‐MT sequence is able to detect biochemical changes in the Achilles tendon after long‐distance running. Level of Evidence: 2 Technical Efficacy: Stage 1